2014
DOI: 10.9734/bjmmr/2014/7247
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Tonometry and Sporadic Creutzfeldt - Jakob disease (sCJD): A Confirmatory Case-Control Study

Abstract: AimsTo evaluate the hypothesis that sporadic Creutzfeldt-Jakob disease (sCJD) may be transmitted through ocular tonometry.BackgroundThe infectious agent of sCJD may be present in the cornea prior to clinical symptoms. Cornea infectiousness has been documented by cornea transplants in guinea pigs and humans. sCJD is resistant to complete inactivity by conventional sterilization techniques. Thus contact tonometry equipment is not disinfected sufficiently to kill sCJD. We previously hypothesized that contact tono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To uncover potential risk factors, researchers have investigated the link between sCJD and surgery (Hamaguchi et al, 2009;van Duijn et al, 1998;Ward et al, 2002Ward et al, , 2008, ocular tonometry (Davanipour et al, 2014b), profession (Hermann et al, n.d.), physical injuries (Kondo & Kuroiwa, 1982), living with pets (Harries-Jones et al, 1988), and dementia in relatives (Harries-Jones et al, 1988). While factors such as needing surgery or dental work are scarcely modifiable, several interesting studies have examined a possible link between sCJD and highly modifiable dietary factors.…”
Section: Potential Scjd Risksmentioning
confidence: 99%
“…To uncover potential risk factors, researchers have investigated the link between sCJD and surgery (Hamaguchi et al, 2009;van Duijn et al, 1998;Ward et al, 2002Ward et al, , 2008, ocular tonometry (Davanipour et al, 2014b), profession (Hermann et al, n.d.), physical injuries (Kondo & Kuroiwa, 1982), living with pets (Harries-Jones et al, 1988), and dementia in relatives (Harries-Jones et al, 1988). While factors such as needing surgery or dental work are scarcely modifiable, several interesting studies have examined a possible link between sCJD and highly modifiable dietary factors.…”
Section: Potential Scjd Risksmentioning
confidence: 99%
“…Previous studies have reported that applanation tonometry has the potential to transmit a variety of infectious agents, including adenovirus 8 and herpes simplex virus 1, and reusable tonometer prisms could, in theory, be a mode of transmission for hepatitis B, hepatitis C, human immunodeficiency virus, and Creutzfeldt-Jakob disease. [31][32][33][34][35][36][37] A systematic review of 11 studies assessing the disinfection of Goldmann tonometers concluded that there is no definitive optimal technique or agent for the disinfection of Goldmann applanation tonometer prisms. 30,33 The AAO supports the use of diluted bleach for the disinfection of reusable tonometer tips for SARS-CoV-2 and adenovirus.…”
Section: Contact Tonometrymentioning
confidence: 99%
“…Davanipour et al 124 postulate that ocular tonometry is a risk factor for contracting sCJD from a case-control study conducted across 11 states in the USA. Contact tonometry is used by ophthalmologists to diagnose glaucoma.…”
Section: Risks In Eye Surgerymentioning
confidence: 99%
“…The authors conclude that disposable covers or non-contact tonometry should be used in the absence of adequate decontamination processes. 124 Tullo et al 125 document that there were three recipients of either cornea or sclera from a woman who died of biopsy-proven carcinoma of the bronchus in 1997, but was later neuropathologically identified as having sCJD. 125 At the time of publication, two recipients remained symptom-free of CJD, whereas one patient had died, aged 92 years (7 years after surgery), showing some signs of dementia that were not considered indicative of iCJD.…”
Section: Risks In Eye Surgerymentioning
confidence: 99%